2007
DOI: 10.1101/gad.1607807
|View full text |Cite
|
Sign up to set email alerts
|

Control of sex-specific apoptosis in C. elegans by the BarH homeodomain protein CEH-30 and the transcriptional repressor UNC-37/Groucho

Abstract: Apoptosis is essential for proper development and tissue homeostasis in metazoans. It plays a critical role in generating sexual dimorphism by eliminating structures that are not needed in a specific sex. The molecular mechanisms that regulate sexually dimorphic apoptosis are poorly understood. Here we report the identification of the ceh-30 gene as a key regulator of sex-specific apoptosis in Caenorhabditis elegans. Loss-of-function mutations in ceh-30 cause the ectopic death of male-specific CEM neurons. ceh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 56 publications
(66 reference statements)
3
73
0
Order By: Relevance
“…The CB1490 males were not different from wild-type males in our bioassays. We used strain CU607 smIs23 [pkd-2::gfp+ pBX]; him-5(e1490) (43) to record responses from GFP-labeled CEM neurons. We crossed this smIs23 transgene into BC168 [unc-13(s69)] to obtain strain PS6327, used to record responses in the unc-13 synaptic mutant background.…”
Section: Methodsmentioning
confidence: 99%
“…The CB1490 males were not different from wild-type males in our bioassays. We used strain CU607 smIs23 [pkd-2::gfp+ pBX]; him-5(e1490) (43) to record responses from GFP-labeled CEM neurons. We crossed this smIs23 transgene into BC168 [unc-13(s69)] to obtain strain PS6327, used to record responses in the unc-13 synaptic mutant background.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in hermaphrodites, TRA-1 ensures survival of hermaphrodite-specific neurons (HSNs) by repressing transcription of egl-1 and ensures death of male-specific neurons (CEMs) by repressing the anti-apoptotic gene ceh-30 (Conradt and Horvitz, 1999;Peden et al, 2007;Schwartz and Horvitz, 2007). Outside of the nervous system, TRA-1 interacts with cell cycle regulators to mediate sex-specific asymmetric division in the gonad and has been reported to regulate fusion of vulval precursor cells by influencing expression of lin-39 (Tilmann and Kimble, 2005;Szab o et al, 2009).…”
Section: The Sex Determination Overlaymentioning
confidence: 99%
“…We found that the CEMs did not inappropriately survive in these animals, indicating that the TRA-1 protein most probably promotes egl-1 transcription indirectly (P Grote and B Conradt; unpublished observation). Indeed, Bob Horvitz, Ding Xue et al have recently shown that TRA-1 acts through the BarH homeodomain transcription factor, CEH-30, to promote egl-1 transcription (Figure 3) (Peden et al, 2007;Schwartz and Horvitz, 2007). Specifically, the transcription of the ceh-30 gene, which was identified as a gene required for the survival of the CEMs in males, is directly repressed by TRA-1 in CEMs.…”
Section: Controlling Egl-1 Activity: Transcriptional Regulation Is Keymentioning
confidence: 99%